ULTRASOUND EXAMINATION POSSIBILITIES IN ADENOMYOSIS DIAGNOSTICS IN PATIENTS WITH REPRODUCTIVE LOSS - A. V. Pomortsev; T. B. Makuhina; Y. V. Grushevskaya (Кубанский научный медицинский вестник, 2018)
Aim. The research was designed to study the possibilities of ultrasound examination with Color Doppler imaging (CDI) and three-dimensional volumetric reconstruction (3D) in the diagnostics of adenomyosis of minimal prevalence in patients with unspecified infertility and reproductive losses at the early stages of gestation. Materials and methods. 40 patients with unspecified infertility and early pregnancy loss (the main group) and 35 healthy patients (the control group) were examined in the course of the study. All patients underwent small pelvic ultrasound in В / CDI / 3D-modes with an assessment of the junctional zone (JZ) on days 5-7 and 18-22 of the menstrual cycle (MC).Results. In the main group, there was a discrepancy between the structure of the endometrium and the phase of the cycle at 5-7 days of the MC, a decrease in vascularization of the JZ at 18-22 days of the MC, a local increase in blood flow in the endometrium in phases 1 and 2 of the MC; the fuzziness of the junctional zone, an increase in min and max thickness of the junctional zone, the difference between them, as well as the ratio of max thickness of the junctional zone to the thickness of the uterus wall regardless of the phase of the MC (p = 0.005; 0.0001; 0.005; 0.03; 0.0004; 0, 0001; 0.0001; 0.0001; 0.0001 respectively).Conclusion. Ultrasonography with the CDI and 3D reconstruction allows us to identify a high-risk group by the presence of a minimal prevalence of adenomyosis in the patients with unspecified infertility and reproductive losses at the early stages of gestation.